Relationship between Anti-European Brown Hare Syndrome Serological Titers and Brown Hare (Lepus europaeus Pallas) Densities - Gisella Paci; Antonio Lavazza; Marco Ferretti; Francesco Santilli; Marco Bagliacca (International Journal of Zoology)
Thirty-three protected wild game reproduction areas, located in the province of Florence (Central Italy), were monitored for habitat characteristics and hare census over a period of 2 years. A total of 172 hares was captured, checked for sex, and age, and blood samples were taken. Serum samples were analyzed by competitive ELISA test for detection and titration of anti-European brown hare syndrome virus (EBHSV) antibodies. Results showed that EBHSV seropositive hares from areas with high and medium population densities had higher antibody titers than those coming from low-density areas and that adults showed lower values than young animals. Anti-EBHSV antibody levels were inversely related to the distances between protected areas and private hunting areas while a high density of protected areas was not associated with any similarity in the values or prevalence of EBHSV.